Contribution of Organizational Structure on Strategy Implementation in Kenya Government Tourism Agencies - Kyalo, Juliana (Journal of Strategic Management, 2023)
Purpose: The purpose of this study was to examine the contribution of organizational structure on strategy implementation in Kenya government tourism agencies. Methodology: The study used a positivist approach research philosophy. The research designs employed in this study were explanatory and descriptive research designs. The study population comprised of the tourism industry. The study included the ministry of tourism itself since it is the parent ministry that regulates and oversees the operations of the tourism agencies to give a total of 10 areas of study. A sample of 327 was achieved based on the following formula. This study used primary data. The study used questionnaires and interview guides to collect both qualitative and quantitative data. Quantitative data was analyzed through scientific methods while qualitative data was analyzed thematically. The descriptive statistics was first used to analyze the demographic factors of the respondents using frequencies and charts. Inferential statistics such as correlation and multiple linear regression analysis were used to test the relationship among the variables as per the study hypothesis. Findings: The structure of an organization was found to have significant effect on the realization of objectives and profits in an organization. The organizational functions and targets, the structure of employee learning and growth and systems of communications have an influence on how organizations achieve their objectives and their profits. Culture also has been found to play its critical role in implementation of strategies and consequently realizations of set objectives and profits in organizations. Organizational norms, ethics, employee training and organizational climate are very key in achieving success while implementing strategies. Unique Contribution to Theory, Practice and Policy: To effectively implement strategies in the tourism industry, the organizational structures need to have lines of communication, simple layer of reporting, flexible structure and good systems which ensure quick decision making in organizations.